2014
DOI: 10.5424/sjar/2014124-5462
|View full text |Cite
|
Sign up to set email alerts
|

Impact of infiltration parameters and Manning roughness on the advance trajectory and irrigation performance for closed-end furrows

Abstract: Abbreviations used: AAE (average absolute error); ARE (average relative error); DE (differential evolution); Du (distribution uniformity); Ea (application efficiency); Es (storage efficiency); KW (kinematic-wave); RE (relative error); ZI (zero-inertia).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 27 publications
2
10
0
Order By: Relevance
“…The simulated values of the advance time and performance indicators had a slight influence when the various Manning's roughness values (0.041, 0.075, and 0.175) were adopted (Figure 4), indicating that the advance trajectory and performance indicators of closed-end furrow irrigation were not sensitive to variations of Manning's roughness. This result was similar to the results of Smith et al [2], Salahou et al [5], and Nie et al [19]. These findings indicate that the Manning roughness of maize field can be used as a representative value (i.e., 0.075, 50% of the cumulative frequency of all experimental sites) to simulate the advance trajectory and irrigation performance of a closed-end furrow.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The simulated values of the advance time and performance indicators had a slight influence when the various Manning's roughness values (0.041, 0.075, and 0.175) were adopted (Figure 4), indicating that the advance trajectory and performance indicators of closed-end furrow irrigation were not sensitive to variations of Manning's roughness. This result was similar to the results of Smith et al [2], Salahou et al [5], and Nie et al [19]. These findings indicate that the Manning roughness of maize field can be used as a representative value (i.e., 0.075, 50% of the cumulative frequency of all experimental sites) to simulate the advance trajectory and irrigation performance of a closed-end furrow.…”
Section: Discussionsupporting
confidence: 89%
“…Zhang et al [11], Bautista et al [12], and Anwar et al [13] have reported Manning's roughness values of 0.02-0.40, 0.04-0.10, and 0.04-0.16, respectively. Other published studies have often used a representative value of Manning's roughness to simulate furrow irrigation [14][15][16][17][18][19]. The question of whether the simulated values correspond well to practical field performance, i.e., the effects of the dependence of Manning roughness on the advance trajectory and irrigation performance of closed-end furrows are rarely analyzed comprehensively, especially at regional scales.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the actual situation, it is reasonable to assume that the maximum Zf is 100 cm under surface irrigation. Moreover, the water depth, h0, usually ranges from 5 to 10 cm under surface irrigation [32,33], and the value of the suction head, ψm, is a nonnegative number in the GA model (Equation (1)). Thus, on the basis of all the aforementioned analyses, the maximum value of L * is less than 20, according to Equation (6).…”
Section: ( )mentioning
confidence: 99%
“…Various studies have reported that the infiltration equation is affected by initial soil water content and irrigation water quality (Amézketa et al, ; Nie et al, ; de Almeida et al, ). In many cases, the infiltration equation is assumed constant during the irrigation season, while the soil water content is changing throughout the season (Hunsaker et al, ; Emdad et al, ).…”
Section: Introductionmentioning
confidence: 99%